2021
DOI: 10.1148/rg.2021200075
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic Features of Type II and Type XI Collagenopathies

Abstract: Type II collagen is a major component of the cartilage matrix. Pathogenic variants (ie, disease-causing aberrations) in the type II collagen gene (COL2A1) lead to an abnormal structure of type II collagen, causing a large group of skeletal dysplasias termed type II collagenopathies. Because type II collagen is also located in the vitreous body of the eyes and inner ears, type II collagenopathies are commonly associated with vitreoretinal degeneration and hearing impairment. Type II collagenopathies can be radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Spondyloepiphyseal dysplasia congenita (SEDC) is the most common short-trunked bone dysplasia with predominant involvement of the spine and the epiphyses [ 10 , 11 ]. SEDC is the common condition among type II collagenopathies—a group of disorders caused by abnormal type II collagen [ 12 ]. A clinical feature includes short stature varying in severity, predominantly caused by a short trunk and short neck.…”
Section: Spondyloepiphyseal Dysplasia Congenitamentioning
confidence: 99%
“…Spondyloepiphyseal dysplasia congenita (SEDC) is the most common short-trunked bone dysplasia with predominant involvement of the spine and the epiphyses [ 10 , 11 ]. SEDC is the common condition among type II collagenopathies—a group of disorders caused by abnormal type II collagen [ 12 ]. A clinical feature includes short stature varying in severity, predominantly caused by a short trunk and short neck.…”
Section: Spondyloepiphyseal Dysplasia Congenitamentioning
confidence: 99%
“…PPARγ plays a role in the regulation of matrix decomposition ( Afif et al, 2007 ). Previous reports showed that collagen II is a major component of the cartilage matrix ( Handa et al, 2021 ). MMP-13 can hydrolyze collagen II, which is considered as a significant biomarker to assess OA therapeutic effects and OA progression ( Corciulo et al, 2017 ).…”
Section: Results and Disussionmentioning
confidence: 99%
“…One of the consequences of genetically determined anomalies of type II collagen synthesis, which include numerous congenital anomalies of the development of epiphyses under the general term «epiphyseal dysplasias» (ED) [1][2][3][4], is the development of early osteoarthritis, accompanied by a corresponding decrease in the quality of life and an increase in the need in medical and social assistance [2,[5][6][7][8][9][10]. According to published information [1,3,4,[10][11][12], 5-29 % of the population have phenotypic signs of various types of collagenopathies with clinically expressed lesions of the musculoskeletal system, and osteoarthritis is steadily progressing on their basis. There is currently no etiological therapy for this impairment, which reduces the treatment of patients to slowing down the progression of osteoarthritis through symptomatic therapy with the timely application of radical treatment methods in order to preserve the social adaptation of patients [5,6,9,10,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%